Pengaruh Variasi HPMC dan Carbopol pada Formulasi Sedian Gel Ekstrak Daun Namnam (Cynometra cauliflora L.) terhadap Methicillin-resistant Staphylococcus aureus (MRSA) - Syarah Anliza; Hamtini Hamtini; Nurmeily Rachmawati (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2024)
Antiseptic gel is a hand sanitizer that is useful for cleaning or eliminating germs on hands. One of the most important thing in antiseptic is antibacteria substances that had potential to destroy germs. Namnam leaves are an alternative for making antiseptic gel because they contain alkaloids and flavonoids. Making gel requires gel-forming materials such as HPMC and Carbopol. The aim of this research is to test the effect of gelling agents HPMC and Carbopol on namnam leaves extract as a gel sanitizer preparation and its ability to fight Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria which is a to interfere human health because it causes various infections that are difficult to treat. This research uses the maceration method in the extraction process, disc diffusion in the bacterial inhibition test, pH test, spreadability test, and homogeneity test on the gel sanitizer preparation. The conclusion of this research is that the gelling agent HPMC has the greatest active ability compared to Carbopol which is characterized by an inhibitory power of 14 mm at a variation of 0.25 grams. Increasing variations in HPMC and Carbopol will increase viscosity and reduce spreadability and inhibitory power against bacteria.